Ten‐Year Assessment Encourages No‐Till for Corn Grain and Stover Harvest. Issue 1 (1st September 2018) - Obrycki, John F.; Kovar, John L.; Karlen, Douglas L.; Birrell, Stuart J.
Abstract : Core Ideas: No‐till with 35% stover removal met corn grain yield, income, and soil protection goals. Profitability for no‐till and chisel plow systems were equal due to lower machinery costs. Cost‐efficient stover harvest is essential for bio‐economy development. Developing a bio‐economy by harvesting crop residues from highly productive corn ( Zea mays L.) cropping systems requires science‐based management decisions to maintain or enhance grain yield and soil, water, and air resources. Which tillage and stover harvest practices are best for accomplishing these goals? Continuous corn grain yield response to either no‐till or chisel plowing with two stover harvest rates (3.4 or 5.1 Mg ha −1 yr −1 ) was evaluated for 10 yr in central Iowa. Each tillage and stover removal combination was replicated four times. Year‐to‐year variation affected grain yield more than tillage practice (0.2 Mg ha −1 ) or stover removal (0.1 Mg ha −1 ). Grain yields were not statistically different ( p = 0.33) between tillage systems. Including machinery costs made return on investment for chisel plow and no‐till equivalent even though no‐till yields were numerically lower. Net stover income per megagram was US2 to 4 greater at the 3.4 versus 5.1 Mg ha −1 harvest rate because of more efficient harvesting. Among the four practices, no‐till with 3.4 Mg ha −1 stover harvest met multiple goals, including providing acceptable corn grain yields, positive net income per megagram stover, and sufficient residues to protect the soil.